2022
DOI: 10.1093/glycob/cwac005
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonization and TH17 immunity are shaped by intestinal sialylation in neonatal mice

Abstract: Interactions between the neonate host and its gut microbiome are central to the development of a healthy immune system. However, the mechanisms by which animals alter early colonization of microbiota for their benefit remain unclear. Here, we investigated the role of early-life expression of the α2,6-sialyltransferase ST6GAL1 in microbiome phylogeny and mucosal immunity. Fecal, upper respiratory, and oral microbiomes of pups expressing or lacking St6gal1 were analyzed by 16S rRNA sequencing. At weaning, the fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…Hepatic expression of ST6GAL1 is under the control of glucocorticoids [33] and cytokines that remain incompletely defined [33,34]. Many other cells and tissues also release ST6GAL1 into their environment, including lactating mammary glands [35], neonatal intestinal epithelium [36,37] and mature B cells [38]. Cancer cells, most notably lung, colon and breast express and release copious quantities of ST6GAL1 [39][40][41][42][43].…”
Section: Modes Of Sialylationmentioning
confidence: 99%
“…Hepatic expression of ST6GAL1 is under the control of glucocorticoids [33] and cytokines that remain incompletely defined [33,34]. Many other cells and tissues also release ST6GAL1 into their environment, including lactating mammary glands [35], neonatal intestinal epithelium [36,37] and mature B cells [38]. Cancer cells, most notably lung, colon and breast express and release copious quantities of ST6GAL1 [39][40][41][42][43].…”
Section: Modes Of Sialylationmentioning
confidence: 99%
“…The gut microbiota can also mediate Th17 responses. A study found that microbiome-dependent Th17 inflammation is regulated by α2,6-sialyl ligands, where α2,6-sialyltransferase deficiency induced mucosal Th17 responses [72]. Pathological Th17 cells can also be promoted by the Actinobacterium Eggerthella lenta through help by the cardiac glycoside reductase 2 enzyme [73] and Fusobacterium nucleatum via the short-chain fatty acid, butyrate [74].…”
Section: Interaction Between Gut Microbiota and Adaptive Immune Systemmentioning
confidence: 99%
“…Additionally, Th17 responses can also be influenced by the gut microbiota [ 38 ]. The microbiome-dependent Th17 inflammation is regulated by α2,6-sialyl ligands; α2,6-sialyltransferase deficiency can induce mucosal Th17 responses [ 39 ]. Actinobacterium Eggerthella lenta can also promote pathological Th17 cells through the cardiac glycoside reductase 2 enzyme.…”
Section: The Molecular Role Of the Gut Microbiota In Asthma Pathogenesismentioning
confidence: 99%